2018
DOI: 10.1093/neuonc/noy009
|View full text |Cite
|
Sign up to set email alerts
|

Targeted next-generation sequencing for differential diagnosis of neurofibromatosis type 2, schwannomatosis, and meningiomatosis

Abstract: Simultaneous investigation of NF2, SMARCB1, LZTR1, and SMARCE1 is a key element in the differential diagnosis of NF2, schwannomatosis, and meningiomatosis. The targeted NGS strategy is suitable for the identification of NF2 mosaicism in blood and for the investigation of tumors from these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…Patient 4 harbored c.764 T > G variant in exon 8 corresponding to the predicted missense p.(Leu255Arg). This patient’s variant was already reported [16]. This variant was not described in population databases and was predicted deleterious by several prediction softwares leading to a variant of unknown significance classification according to the American College of Medical Genetics recommendations [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient 4 harbored c.764 T > G variant in exon 8 corresponding to the predicted missense p.(Leu255Arg). This patient’s variant was already reported [16]. This variant was not described in population databases and was predicted deleterious by several prediction softwares leading to a variant of unknown significance classification according to the American College of Medical Genetics recommendations [20].…”
Section: Resultsmentioning
confidence: 99%
“…DNA was isolated from peripheral blood leucocytes using the Maxwell® 16 system and Maxwell® 16 LEV Blood DNA Kit (Promega). NF2 , SMARCB1 and LZTR1 genes were investigated on the next-generation sequencing (NGS) facility of Cochin Hospital in Paris, France as already reported by Louvrier et al [16] Briefly, a custom Ampliseq panel targeting the coding sequences of these genes was designed using the Ampliseq Designer plugin [17]. Preparation of NGS libraries, amplification, purification, emulsion PCR, enrichment, loading on Ion 316™ chips, sequencing with an Ion Personal Genome Machine® (PGM™) System (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most well-described genetic alteration is a mutation in the SMARCB1 gene or LZTR1 gene on chromosome 22q11.2. 13 In our case, these mutations were not present and instead a mutation in SOX10 was observed. While SOX10 has been used previously as an identifying marker for schwannomas, mutation of SOX10 as a contributor to the pathogenesis of schwannomatosis, to our knowledge, has not been previously reported.…”
Section: Discussionmentioning
confidence: 43%
“…It has been shown that 48% of familial and 9.8% of sporadic patients with schwannomatosis exhibit germline SMARCB1 mutations (Boyd et al, 2008;Hadfield et al, 2008;Hulsebos et al, 2007;Rousseau, Noguchi, Bourdon, Sobol, & Olschwang, 2011;Sestini, Bacci, Provenzano, Genuardi, & Papi, 2008;Smith, Wallace, Bowers, Eaton, & Evans, 2014;Smith et al, 2012). Genetic heterogeneity is observed in schwannomatosis since germline mutations in LZTR1 have also been identified in patients with the disease (Hutter et al, 2014;Louvrier et al, 2018;Paganini et al, 2015;Piotrowski et al, 2012;Smith et al, 2015). Furthermore schwannomatosis predisposition genes are likely to exist since germline mutations in SMARCB1 or LZTR1 are not detectable in at least 50% of sporadic patients with schwannomatosis (Kehrer-Sawatzki, Farschtschi, Mautner, & Cooper, 2017).…”
Section: Introductionmentioning
confidence: 99%